Study of role of low molecular weight heparin in conjunction with conventional therapy in severe acute pancreatitis - Rojaramani Kumbha; Sobharani Bathena; Hari Babu Mekala Anand; Venkat Vineeth Amavasya (Asian Journal of Medical Sciences, 2022)
Background: Acute pancreatitis is a disease which has many etiologies. Each etiology seems to affect the pancreatic acinar cell in some way that results in premature activation and retention of potent proteolytic enzymes. Low molecular weight heparin (LMWH) is known to reduce the release the cytokines and inflammatory mediators and result in the improvement of microcirculation of pancreas.